Answer:
1 + ln 2 - ln x
Step-by-step explanation:
ln ( 2e /x)
We know that ln ( a/b) = ln ( a) - ln (b)
ln (2e) - ln (x)
We also know that ln ( a*b) = ln a + ln b
ln ( 2) + ln e - ln x
We know that the ln e = 1
ln 2 + 1 - ln x
Changing the order
1 + ln 2 - ln x
Answer:
-3
Step-by-step explanation:
answer: you're missing the problem
Answer:
step 3: he should have divided both sides by -7
Answer: The answer is not -7 it is in fact -31.
Step-by-step explanation:
5 - ( 6^2 ) / 4 - 3
6^2 = 36
5 - ( 6^2 ) = -31
4 - 3 = 1
5 - 36 / 1 = -31 / 1 = -31
So anything divided by 1 is = to itself.